Analysis of Plant Leaf Disease Based on Sensor and Machine Learning Technique - Chakole, Saurabh S.; Khera, Shelej; Ukani, Neema Amish (2022 IEEE International Conference on Current Development in Engineering and Technology (CCET), 2022)
Plant disease detection is crucial in the field of agriculture as it impacts yield and overall production. Due to the above mentioned issue going to impact the food supply chain. Agriculture is a primary source for food generation thus there is a need to provide the cost effective solution for leaf disease detection. There are various techniques to detect a leaf disease in which image or numerical based data extraction is widely used due to its accuracy. Thus low cost flexible leaf sensor integrated with the above method is suitable to resolve the afar mentioned Challenge. This paper explores the advantages of low cost sensor over the reported work and hybrid machine-learning (H.M.L) algorithm is proposed for disease detection.